1983
DOI: 10.3109/00365528309181836
|View full text |Cite
|
Sign up to set email alerts
|

A Predictor Analysis of Clinical Assessment of Outcome among Patients Operated on for Duodenal Ulcer

Abstract: During a period of 1 year, data concerning life events, non-specific psychological symptoms, individual social history, and ulcer history were obtained for consecutive cases of patients about to have elective surgical treatment for duodenal ulcer. At the 1-year follow-up examination a blind, clinical evaluation was performed (dumping, dyspepsia, recurrence, and Visick grading), and information concerning the 94 patients' assessment of outcome was obtained. A multivariate predictor analysis was performed. Most … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1987
1987
1990
1990

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…The soeiomedical interview held before start of the lithi um treatment included data on family background variables and life events during upbringing, soeial and geographical mobility, present social background and aetivity, soeial network and support, level of information about the treatment, consumption of drugs, alcohol and eigarettes, and life events which had occurred during a 12-month period prior to the start of the prophylactic lithium treatment. The social and psychosocial parameters in the interview schedule had earlier been applied in an analysis of predictors of outcome (Aagaard et al, 1983). For a comparison of these two patient groups, see Aagaard et al, 1987.…”
Section: Methodsmentioning
confidence: 99%
“…The soeiomedical interview held before start of the lithi um treatment included data on family background variables and life events during upbringing, soeial and geographical mobility, present social background and aetivity, soeial network and support, level of information about the treatment, consumption of drugs, alcohol and eigarettes, and life events which had occurred during a 12-month period prior to the start of the prophylactic lithium treatment. The social and psychosocial parameters in the interview schedule had earlier been applied in an analysis of predictors of outcome (Aagaard et al, 1983). For a comparison of these two patient groups, see Aagaard et al, 1987.…”
Section: Methodsmentioning
confidence: 99%
“…Earlier studies focusing on stressful life events and peptic ulcer disease have failed to show any influence of such events on the course of the disease [22–24]. However, a recent study [25] showed that even if ulcer patients and controls experienced a similar number of potentially stressful life events, ulcer patients perceived their events more negatively by having a significantly lower ego‐strength and coping ability.…”
Section: Discussionmentioning
confidence: 99%
“…[37], Preoperatively and 1 year after the operation, UD patients were asked questions about twenty-two nonspecific psy chological symptoms. Compared with an age-and sex-matched population group, the absolute frequency of affirmative answers were high.…”
Section: Peptic Ulcermentioning
confidence: 99%